## Write an expression to describe the sequence below. Use n to represent the position of a term in the sequence, where n = 1 for the first ter

Question

Write an expression to describe the sequence below. Use n to represent the position of a term in the sequence, where n = 1 for the first term.

-6, -5, -4, -3, …

in progress 0
1 week 2021-09-10T13:38:01+00:00 1 Answer 0

The expression to describe this sequence is Aₙ =  (n – 1) * 1  – 6

Step-by-step explanation:

1. Let’s write an expression to describe the sequence which first four terms are as follows:

– 6, -5, -4, – 3…..

Aₙ = (n – 1) * 1  – 6; A₁ = – 6

A₁ = (n – 1) * 1  – 6 = (1 – 1) * 1  – 6 = 0 * 1 – 6 ⇒A₁ = – 6

A₂ = (n – 1) * 1  – 6 = (2 – 1) * 1  – 6 = 1 * 1 – 6⇒ A₁ = – 5

A₃ = (n – 1) * 1  – 6 = (3 – 1) * 1  – 6 = 2 * 1 – 6⇒ A₁ = – 4

A₄ = (n – 1) * 1  – 6 = (4 – 1) * 1  – 6 = 3 * 1 – 6⇒ A₁ = – 3

A₅ = (n – 1) * 1  – 6 = (5 – 1) * 1  – 6 = 4 * 1 – 6⇒ A₁ = – 2

A₆ = (n – 1) * 1  – 6 = (6 – 1) * 1  – 6 = 5 * 1 – 6⇒ A₁ = – 1

A₇ = (n – 1) * 1  – 6 = (7 – 1) * 1  – 6 = 6 * 1 – 6⇒ A₁ = 0